Chrono-Resistance Training Optimizes Hippocampal Oxidative Balance, Reduces Visceral Fat, and Enhances Memory in Healthy Rats Model: Preliminary Findings - Anuar, Nur Aisyah; Abdul Karim, Norwahidah; Mohd Nazri, Nurul Hazlini Suhaida; Laililnizan, Muhammad Halil Fikri; Ibrahim, Farah Wahida; Fairof, Muhammad Hafiz Zuhdi; Ahmad Abdullah, Amirul Hafiz; Joseph, Daren Kumar; Al-Saraf, Hameed Ali; Rajab, Nor Fadilah; Mat Ludin, Arimi Fitri (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Exercise acts as a non-photic zeitgeber and reduces visceral adiposity, a key source of oxidative stress that impairs hippocampal integrity and cognitive function. Excess visceral fat promotes systemic redox imbalance, compromising hippocampal-dependent spatial memory. Early oxidative disturbances preceded overt pathology and may contribute to neurodegenerative risk, and exercise may alleviate its risk. However, the metabolic and cognitive outcomes are rarely assessed together in resistance exercise models. Therefore, this study investigated chronoresistance training effects on visceral fat, hippocampal oxidative status, and spatial memory in healthy rats.METHODS: Wistar rats were assigned to Early-active Control (EC), Early-active Exercise (EE), Late-active Control (LC), and Late-active Exercise (LE). Exercise was performed three times per week for 8 weeks along a 180-cm ladder-climbing track. Before and after the exercise protocol, the rats’ grip strength, visceral fat mass, and spatial memory (Y-maze) were assessed. Hippocampal oxidative markers, including malondialdehyde (MDA) and glutathione (GSH) were also measured with thiobarbituric-acid-reactive-substances (TBARS) assay and modified Ellman method, respectively.RESULTS: At week-8, LC showed greater grip strength than EC (p=0.002), while EE maintained higher strength than EC (p<0.001). LC reduced visceral fat compared with EC (p<0.001), with further reductions in EE (p<0.001). Hippocampal MDA was lower in EE and LC than LE (p≤0.002), whereas GSH was highest in EE (p<0.001). Spatial memory declined in EC (p=0.004) but improved in LC (p=0.015), with LC outperforming EC (p<0.001).CONCLUSION: Rats assigned to EE chrono-resistance training shows better results in improving grip strength, adiposity, and redox balance, whereas LC chrono-resistance training shows better results in preserving spatial working memory. This suggests that chrono-resistance training improves metabolic and hippocampal redox outcomes and modulates memory, indicating that exercise timing shapes metabolic–brain adaptations.KEYWORDS: chrono-exercise, grip strength, hippocampus, memory cognition, oxidative stress, visceral fat